Epidemiology of atrial fibrillation and risk of CVD mortality among hypertensive population: A prospective cohort study in Northeast China - Du, Zhi; Lin, Min; Tian, Yuanmeng; Jing, Li; Liu, Shuang; Li, Guangxiao; Jia, Tong; Sun, Qun; Shi, Lei; Sun, Jixu; Tian, Wen; Xing, Liying (Frontiers in Cardiovascular Medicine, 2022)
Background Determining risk factors of cardiovascular disease (CVD)-related mortality and evaluating their influence are important for effectively reducing corresponding mortality. However, few research findings have estimated the relationship between atrial fibrillation (AF) and CVD-related mortality among hypertension individuals. Objective The objective of this study was to investigate the epidemiology of AF in a hypertension population and determine the relationship between AF and CVD-related mortality. Methods Using a multistage, stratified, and cluster random sampling method, the prospective cohort study with a median follow-up of 3.51 years enrolled 10,678 hypertensive participants at baseline. The prevalence, awareness, and anticoagulation data of AF in this focal population were carefully assessed. Stepwise logistic regression and Cox regression analysis were respectively performed to evaluate the determinants of AF and the association between AF and CVD-related mortality. Results The overall prevalence of AF was 1.3% (95% CI, 1.1%−1.6%) in the hypertensive population, and it was higher in men than in women (1.8% vs. 1.0%, respectively; p=0.001). The awareness of AF was 53.1%, and the rate of oral anticoagulant (OAC) therapy was only 4.2%, although all AF participants should have required according to the European Society of Cardiology guidelines. The determinants of AF included elder, male, and history of coronary heart disease in the hypertensive population. Besides, compared with individuals without AF, the risk of CVD-related mortality significantly increased in the hypertensive population with AF (HR 3.37, 95% CI 2.10–5.40). Conclusion Our results indicated a huge burden of AF and underuse of OAC therapy for them in a community-based hypertensive population. Considering that most of the risk factors of AF were unmodifiable in hypertensive individuals, as well as its high risk of mortality, long-term interventions including AF education, timely screening, and widespread use of OACs should be emphasized in the focal populations.